Perfused human hepatocyte microtissues identify reactive metabolite-forming and mitochondria-perturbing hepatotoxins. (February 2018) - Rowe, Cliff; Shaeri, Mohsen; Large, Emma; Cornforth, Terri; Robinson, Angela; Kostrzewski, Tomasz; Sison-Young, Rowena; Goldring, Christopher; Park, Kevin; Hughes, David
Abstract: Hepatotoxins cause liver damage via many mechanisms but the formation of reactive metabolites and/or damage to liver mitochondria are commonly implicated. We assess 3D human primary hepatocyte microtissues as a platform for hepatotoxicity studies with reactive metabolite-forming and mitochondria-perturbing compounds. We show that microtissues formed from cryopreserved human hepatocytes had bile canaliculi, transcribed mRNA from genes associated with xenobiotic metabolism and expressed functional cytochrome P450 enzymes. Hierarchical clustering was used to distinguish dose-dependent hepatotoxicity elicited by clozapine, fialuridine and acetaminophen (APAP) from control cultures and less liver-damaging compounds, olanzapine and entecavir. The regio-isomer of acetaminophen, N -acetyl-meta-aminophenol (AMAP) clustered with the hepatotoxic compounds. The principal metabolites of APAP were formed and dose-dependent changes in metabolite profile similar to those seen in patient overdose was observed. The toxicological profile of APAP was indistinguishable from that of AMAP, confirming AMAP as a human hepatotoxin. Tissue oxygen consumption rate was significantly decreased within 2 h of exposure to APAP or AMAP, concomitant with glutathione depletion. These data highlight the potential utility of perfused metabolically functional human liver microtissues in drug development and mechanistic toxicology. Graphical abstract: Highlights: 3D microtissues of human hepatocytes express functional cytochrome P450 enzymes. Microtissues can be used to identify hepatotoxic compounds. A metabolic profile for acetaminophen similar to that in patients was observed. N -acetyl-meta-aminophenol confirmed as a human hepatotoxicant